EFEKTIVITAS MODEL BLENDED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PAI DAN BUDI PEKERTI DI KELAS XI IPS SMA N 2 TELUK KUANTAN KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI (TP 2020/2021) - Wilia Anggraini; Sarmidin Sarmidin; Helbi Akbar (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
This research is motivated by blended learning which is not a new thing in the world of education, especially related to 21st century learning which is changing rapidly. This research is a quantitative study with a qusai experiment in the form of a nonequivalent control group design, which was carried out at SMA Negeri 2 Teluk Kuantan, Munsalo Kopah Village. The data collection technique used is a questionnaire with questionnaire instruments, interviews and documentation. Data analysis using SPSS 20 software. The results of this study indicate that the positive and significance of the blended learning model, the significance test found the equation that the value of sig. (2-tailed) 0.000 < from a probability of 0.05 so that there is an effectiveness of the blended learning model on student learning outcomes.